2020
DOI: 10.3847/1538-4365/ab67b6
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrogenated Polycyclic Aromatic Hydrocarbon Molecules: Vibrational Spectra in the Infrared

Abstract: Superhydrogenated polycyclic aromatic hydrocarbons (PAHs) may be present in H-rich and ultraviolet-poor benign regions. The addition of excess H atoms to PAHs converts the aromatic bonds into aliphatic bonds, the strongest of which falls near 3.4 µm. Therefore, superhydrogenated PAHs are often hypothesized as a carrier of the 3.4 µm emission feature which typically accompanies the stronger 3.3 µm aromatic C-H stretching feature. To assess this hypothesis, we use density function theory to compute the infrared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…By comparing Figure 7 with Figure 6, one immediately sees that, in comparison with their neutral counterparts, in cations both the C-D and C-H stretches are substantially suppressed while the C-C stretches are considerably enhanced. Such suppression in C-H stretches and enhancement in C-C stretches have also been seeen in pure PAHs (e.g., see Allamandola et al 1999), mono-deuterated PAHs (Yang et al 2020b), superhydrogenated PAHs (Yang et al 2020a) and PAHs with aliphatic functional groups (Yang et al 2017). Moreover, the C-D and C-H stretches of cationic species appear to occur at a somewhat shorter wavelength compared with their neutral counterparts.…”
Section: Multi-deuterated Pyrenementioning
confidence: 78%
See 2 more Smart Citations
“…By comparing Figure 7 with Figure 6, one immediately sees that, in comparison with their neutral counterparts, in cations both the C-D and C-H stretches are substantially suppressed while the C-C stretches are considerably enhanced. Such suppression in C-H stretches and enhancement in C-C stretches have also been seeen in pure PAHs (e.g., see Allamandola et al 1999), mono-deuterated PAHs (Yang et al 2020b), superhydrogenated PAHs (Yang et al 2020a) and PAHs with aliphatic functional groups (Yang et al 2017). Moreover, the C-D and C-H stretches of cationic species appear to occur at a somewhat shorter wavelength compared with their neutral counterparts.…”
Section: Multi-deuterated Pyrenementioning
confidence: 78%
“…Such a wavelength mismatch had been long noted by Sakata et al (1990) and Kwok & Zhang (2013) for pure PAH molecules of which the C-H stretches lie shortward of the observed wavelength. Perhaps the wavelength mismatch could be accounted for by PAHs including substituents (e.g., N in place of C; see , Mattioda et al 2008 or superhydrogenation (Bernstein et al 1996, Thrower et al 2012, Sandford et al 2013, Yang et al 2020a, Cruz-Diaz et al 2020. It is well recognized that upon substitution, the central wavelengths of the C-C and C-H bands of PAHs appreciably shift.…”
Section: Discussion and Astrophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also with AKARI/IRC, Doney et al (2016) have performed a deuterated PAH survey in 53 Hii regions in the Milky Way, Large Magellanic Cloud and Small Magellanic Cloud. They reported the detection of deuterated PAHs in six sources, as revealed by, in addition to the 5 We note that interstellar PAHs could be superhydrogenated (Bernstein et al 1996, Sandford et al 2013, Yang et al 2020 or attached with aliphatic functional groups (Geballe et al 1985, Sandford 1991, Kwok & Zhang 2011, Yang et al 2017) which could convert the aromatic C atoms to aliphatic. However, we have shown that the degree of superhydrogenation (Yang et al 2020) and the aliphatic content of PAHs are minor (Li & Draine 2012, Yang et al 2013.…”
Section: Aromatic C-h and C-d Band Intensities Of Deuterated Pahsmentioning
confidence: 88%
“…The C-H stretch also shows a similar behavior for both pure and deuterated PAHs, with an average wavelength of ∼ 3.25 µm for the neutrals and ∼ 3.22 µm for the cations. Meanwhile, the C-D and C-H stretches of the cations are significantly suppressed with respect to the neutrals, just like pure PAHs (e.g., see Allamandola et al 1999), superhydrogenated PAHs (Yang et al 2020) and PAHs with aliphatic functional groups (Yang et al 2017). Let A 3.3 and A 4.4 respectively be the intrinsic band strengths of the aromatic C-H and C-D stretches on a per bond basis.…”
Section: Mono-deuterated Pahsmentioning
confidence: 99%